Fungos do trato digestório de ovinos melhoram a digestibilidade in vitro da torta de macaúba - Valdo Soares Martins Júnior (2023)
With the constant fluctuation in the prices of commonly used ingredients in formulating ruminant diets, the use of industrial by-products becomes appealing as they provide the necessary nutrients at a reduced cost. Ruminant digestive tract fungi can hydrolyze lignocellulosic materials, promoting better nutrient utilization in diets containing by-products. In this study, the objectives were to analyze the action of fungi from the digestive tract of sheep in the utilization of Macaúba cake (MC) and to evaluate the in vitro digestibility of this by-product inoculated with selected cellulolytic fungi isolates. Initially, the study assessed which fungi exhibited better degradability rates of TM during the submerged fermentation process. Fermentations were conducted in tubes containing distilled water and TM as a nutrient source. The final pH, fungal biomass, and substrate degradability were evaluated. Fungi that demonstrated higher degradability values and biomass production during the fermentation process were Aspergillus fumagatus, Trichoderma longibrachiatum, and Paecilomyces sp., with degradability rates of 6.55%, 5.58%, and 4.80%, respectively. Biomass production results were 4.921 g/L, 3.880 g/L, and 3.512 g/L, respectively. The Aspergillus fumagatus isolate was not selected for the digestibility test due to its pathogenic potential, which would make its use as a microbial additive unfeasible. Subsequently, the in vitro coefficients of dry matter digestibility (IVDMS) and neutral detergent fiber (IVNDFD) of TM inoculated with isolates of Trichoderma longibrachiatum and Paecilomyces sp., or their mixture, were analyzed. The group inoculated with the fungal mixture showed an increase in IVDMS and IVNDFD of 19.75% and 38.51%, respectively, compared to the control group. Thus, the addition of this microbial mixture indicates promising potential for developing microbial additives for supplementation in sheep fed with by-products with high fiber content.